2014
DOI: 10.1128/iai.00916-13
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes Arginine and Citrulline Catabolism Promotes Infection and Modulates Innate Immunity

Abstract: A bacterium's ability to acquire nutrients from its host during infection is an essential component of pathogenesis. For the Gram-positive pathogen Streptococcus pyogenes, catabolism of the amino acid arginine via the arginine deiminase (ADI) pathway supplements energy production and provides protection against acid stress in vitro. Its expression is enhanced in murine models of infection, suggesting an important role in vivo. To gain insight into the function of the ADI pathway in pathogenesis, the virulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
57
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 57 publications
(71 reference statements)
5
57
1
7
Order By: Relevance
“…Common, noninvasive soft tissue infections include bacterial pharyngitis and impetigo, in addition to the less common but invasive and often life-threatening necrotizing fasciitis and immune-pathological syndromes like rheumatic fever (6). It was recently discovered that mutations that blocked the ability of S. pyogenes to catabolize arginine attenuated virulence in a murine model of soft tissue infection (5). However, mutants that block catabolism of citrulline resulted in hyperattenuation (5), revealing an unexpected tissue-specific and arginine-independent role for citrulline metabolism in pathogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Common, noninvasive soft tissue infections include bacterial pharyngitis and impetigo, in addition to the less common but invasive and often life-threatening necrotizing fasciitis and immune-pathological syndromes like rheumatic fever (6). It was recently discovered that mutations that blocked the ability of S. pyogenes to catabolize arginine attenuated virulence in a murine model of soft tissue infection (5). However, mutants that block catabolism of citrulline resulted in hyperattenuation (5), revealing an unexpected tissue-specific and arginine-independent role for citrulline metabolism in pathogenesis.…”
mentioning
confidence: 99%
“…In the Gram-positive pathogen Streptococcus pyogenes (group A streptococcus), it has recently been shown that the ADI pathway metabolite citrulline makes an unexpected arginine-independent contribution to both colonization and virulence (5). This human pathogen is responsible for a large number of diseases that range in severity and invasiveness (6).…”
mentioning
confidence: 99%
“…Экспрессия AД S. pyogenes кодируется опе-роном Arc, который состоит из трех ферментов: ArcA, ArcB, и ArcC, соответствующих АД, орни-тинкарбамоилтрансферазе и карбаматкиназе [19] (рис. 2).…”
Section: иммуносупрессорные эффекты аргининдеиминазыunclassified
“…Карбаматкиназа осуществляет перенос фосфатной группы с карбамоилфосфа-та на ADP, таким образом, синтезируются ATP и NH 3 [18]. В результате из молекулы аргинина образуется одна молекула СО 2 , одна молекула АТФ и две молекулы NH 3 [19]. Предполагаемая роль системы АД состоит в обеспечении бакте-рий ATP, биосинтезе цитрулина или пирими-динов, осуществляемом карбамоилфосфатазой,…”
Section: иммуносупрессорные эффекты аргининдеиминазыunclassified
See 1 more Smart Citation